Bacteria identified in neonatal sepsis cases from a neonatal intensive care unit, Ahmedabad, India - Upasani, Vivek N.; Memakiya, Ajay C.; Patel, Alpesh R.; Patel, Rajat R.; Savalia, Harshitkumar J.; Jhala, Devendrasinh D.; Chettiar, Shiva S. (International Journal of Contemporary Pediatrics, 2026)
Neonatal sepsis (NS) causes mortality in the neonatal intensive care unit (NICU) due to infections by group B Streptococcus (GBS), emerging pathogens and antimicrobial resistance (AMR) strains. This study was undertaken to isolate and identify GBS and other bacteria from cases of neonatal sepsis in a NICU, Ahmedabad, Gujarat. Skin swab samples were collected from neonatal sepsis cases and inoculated in LIM broth. Growth was observed in all the LIM broth tubes inoculated with the sample. Six (6) beta-hemolytic and four (4) non-hemolytic bacteria were isolated on Blood agar plate, and pure cultures were obtained on LB agar plates. These isolates were identified using the Vitek2 system, and 16S rRNA sequencing method. Two (2) isolates, namely NSNH5L and NSNH3S, were identified as Klebsiella pneumoniae (96%) and Staphylococcus haemolyticus (97%), respectively, by the VITEK2 rapid identification system. Antimicrobial susceptibility testing revealed that K. pneumoniae was resistant to aminoglycosides, beta-lactams, and polypeptide antibiotics (Card: AST-N405), except fosfomycin and trimethoprim/sulfamethoxazole; whereas S. haemolyticus was sensitive to most antibiotics, except benzylpenicillin, ciprofloxacin, erythromycin, levofloxacin, gentamicin, and oxacillin (Card: AST-P628). Two (2) isolates, namely, GXDRC_03 (NSH01) and GXDRC_04 (NSH05), were identified as Kocuria arsenatis (99.75%) and Staphylococcus epidermidis (99.59%) based on 16S rRNA sequence homology study. The 16S rRNA sequences have been deposited in GenBank accession nos. PX533098 and PX5331127, respectively. This is the first report on 16S rRNA phylogeny-based identification of bacterial isolates, and isolation of K. arsenatis from neonatal sepsis sample(s) in Gujarat, India.